Relationship between foramen magnum position and locomotion in extant and extinct hominoids. Issue 113 (December 2017) - Neaux, Dimitri; Bienvenu, Thibaut; Guy, Franck; Daver, Guillaume; Sansalone, Gabriele; Ledogar, Justin A.; Rae, Todd C.; Wroe, Stephen; Brunet, Michel
Abstract: From the Miocene Sahelanthropus tchadensis to Pleistocene Homo sapiens, hominins are characterized by a derived anterior position of the foramen magnum relative to basicranial structures. It has been previously suggested that the anterior position of the foramen magnum in hominins is related to bipedal locomotor behavior. Yet, the functional relationship between foramen magnum position and bipedal locomotion remains unclear. Recent studies, using ratios based on cranial linear measurements, have found a link between the anterior position of the foramen magnum and bipedalism in several mammalian clades: marsupials, rodents, and primates. In the present study, we compute these ratios in a sample including a more comprehensive dataset of extant hominoids and fossil hominins. First, we verify if the values of ratios can distinguish extant humans from apes. Then, we test whether extinct hominins can be distinguished from non-bipedal extant hominoids. Finally, we assess if the studied ratios are effective predictors of bipedal behavior by testing if they mainly relate to variation in foramen magnum position rather than changes in other cranial structures. Our results confirm that the ratios discriminate between extant bipeds and non-bipeds. However, the only ratio clearly discriminating between fossil hominins and other extant apes is that which only includes basicranial structures. We show that a large proportion of the interspecific variation in the other ratios relates to changes in facial, rather than basicranial, structures. In this context, we advocate the use of measurements based only on basicranial structures when assessing the relationship between foramen magnum position and bipedalism in future studies.